The Novel β-Lactam Enhancer Zidebactam Augments the In Vivo Pharmacodynamic Activity of Cefepime in a Neutropenic Mouse Lung Acinetobacter baumannii Infection Model - Bhagwat, S. S. (Antimicrob Agents Chemother, 2019)
WCK 5222 is a combination of cefepime and the high-affinity PBP2-binding β-lactam enhancer zidebactam. The cefepime-zidebactam combination is active against multidrug-resistant Gram-negative bacteria, including carbapenemase-expressing Acinetobacter baumannii. The mechanism of action of the combination involves concurrent multiple penicillin binding protein inhibition, leading to the enhanced bactericidal action of cefepime. The aim of the present study was to assess the impact of the zidebactam-mediated enhanced in vitro bactericidal action in modulating the percentage of the time that the free drug concentration remains above the MIC (percent fT>MIC) for cefepime required for the in vivo killing of A. baumannii. Cefepime and cefepime-zidebactam MICs were comparable and ranged from 2 to 16 mg/liter for the A. baumannii strains (n = 5) employed in the study. Time-kill studies revealed the improved killing of these strains by the cefepime-zidebactam combination compared to that by the constituents alone. Employing a neutropenic mouse lung infection model, exposure-response analyses for all the A. baumannii strains showed that the cefepime fT>MIC required for 1-log(10) kill was 38.9%. In the presence of a noneffective dose of zidebactam, the cefepime fT>MIC requirement dropped significantly to 15.5%, but it still rendered a 1-log(10) kill effect. Thus, zidebactam mediated the improvement in cefepime’s bactericidal effect observed in time-kill studies, manifested in vivo through the lowering of cefepime’s pharmacodynamic requirement. This is a first-ever study demonstrating a β-lactam enhancer role of zidebactam that helps augment the in vivo activity of cefepime by reducing the magnitude of its pharmacodynamically relevant exposures against A. baumannii.